A Critical Analysis of Application of Proportionality Test and Margin of Appreciation Doctrine by European Court of Human Rights - Mohammad Jalali; Sogol Soodbar (حقوق بشر, 2022)
European court of human rights was established in 1959 as an independent court of Council of Europe in order to deal with alleged violations of human rights which has been enumerated in European Convention on human rights. Obviously, protection and evolution of human rights obligations is considered as one of the most significant concerns of this court. In addition, the protection of human rights and public interest together Are required for an efficient society. As a result, European court of human rights must use a mechanism by which it can have a reasonable and balanced operation to realize these two fundamental values. In order to approach this aim, the court uses the proportionality test, consisting of three principles of legitimacy, appropriateness and necessity. Despite its efficient results for the Court, the application of this test has its deficiency in keeping a balance between human rights and public interest. This court authorized the member states to evaluate the legitimacy of an aim by themselves, however it should be the court’s task to pass three steps of proportionality test independently. This research mainly concentrates on the evaluation of the European court of human rights from the doctrine of margin of appreciation perspective.